Fractionation of Hepatic Nonparenchymal Cells - Graham, John (ScientificWorldJournal, 2002)
The majority of parenchymal cells from mammalian liver cells can be removed by very low speed centrifugation (50 g) but a simple low-density barrier (1.096 g/ml) is required to remove the remaining parenchymal cells from the 50-g supernatant which contains all of the lower density nonparenchymal cells. Continuous gradients of Nycodenz can provide satisfactory resolution of Kupffer, stellate, and endothelial cells on an analytical basis but the separation of different cell types is not sufficient preparatively. Flotation through a low-density iodixanol barrier can, however, provide a satisfactory enrichment of the least dense nonparenchymal cell – the stellate cells.